Traumatic dislocation of the mandibular condyle into the middle cranial fossa complicated by temporal lobe intracerebral hemorrhage: literature review and our case - Kyrpa, Igor Y.; Sirko, Andrii G.; Komok , Olexiy A. (Ukrainian Neurosurgical Journal, 2019)
Dislocation of the mandibular condyle into the middle cranial fossa is a rare complication of mandibular trauma due to anatomical and biomechanical factors. Due to the proximity of the mandibular condyle to the middle cranial fossa and middle meningeal artery, there is the risk of serious sequelae in case of trauma. The authors report the case of a 31-year-old female patient, who was beaten up in a family dispute. Computer tomography results demonstrated a basilar skull fracture, pneumocephalus, the dislocation of the mandible into the middle cranial fossa. The patient was hospitalized in the neurosurgical department; anti-edema treatment and antibiotic therapy were prescribed. During the first day, deterioration of the condition presented with rising headache and a gradual suppression of consciousness (GCS 13). The control tomography of the brain revealed negative dynamics in the form of development of intracerebral hemorrhage in the right temporal lobe, subdural hematoma to the right and lateral dislocation of the median structures to the left. The patient was operated in critical situation. Right-sided subtemporal approach and cranial trepanation were performed. There were removed numerous bone fragments of a multi-fragile fracture of the petrous part of the right temporal bone. A reposition of the mandibular condyle was performed by pull-through of the latter from the middle cranial fossa. The intracerebral hemorrhage of the right temporal lobe was removed, and a thorough hemostasis was performed. In addition, skull base reconstruction was performed. Rapid diagnosis and a multidisciplinary approach are needed to minimize complications. The modern opportunities of reconstruction of imaging using the CT method were applied. Treatment options should be individualized in case of suspicion of intracranial hematoma formation.